Hyponatremia timing, incidence, and associated risk factors in patients treated with cisplatin for lung cancer: a retrospective study - Ogawa, Sumiaki; Sato, Junya; Tanaka, Rei; Sakakibara, Tatsuya; Shino, Michihiro (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
The incidence of cisplatin-derived hyponatremia remains unknown, although nausea, vomiting, and renal dysfunction are common adverse events of cisplatin, a platinum-based preparation. The factor contributing to hyponatremia are described but not well known. This study aimed to retrospectively investigate the incidence of hyponatremia, timing, and associated risk factors. This study surveyed patients with lung cancer who received cisplatin chemotherapy from August 2013 to July 2019 at Shizuoka Cancer Center. The severity of hyponatremia was evaluated based on Common Terminology Criteria for Adverse Events. A total of 814 patients were included in this study. 682 (83.7%) patients had hyponatremia of any grade: grade 1 (